The pattern of genetic variability in apomictic clones of Taraxacum officinale indicates the alternation of asexual and sexual histories of apomicts - Majeský, Luboš; Vašut, Radim J; Kitner, Miloslav; Trávníček, Bohumil (PLoS One, 2012)
Dandelions (genus Taraxacum) comprise a group of sexual diploids and apomictic polyploids with a complicated reticular evolution. Apomixis (clonal reproduction through seeds) in this genus is considered to be obligate, and therefore represent a good model for studying the role of asexual reproduction in microevolutionary processes of apomictic genera. In our study, a total of 187 apomictic individuals composing a set of nine microspecies (sampled across wide geographic area in Europe) were genotyped for six microsatellite loci and for 162 amplified fragment length polymorphism (AFLP) markers. Our results indicated that significant genetic similarity existed within accessions with low numbers of genotypes. Genotypic variability was high among accessions but low within accessions. Clustering methods discriminated individuals into nine groups corresponding to their phenotypes. Furthermore, two groups of apomictic genotypes were observed, which suggests that they had different asexual histories. A matrix compatibility test suggests that most of the variability within accession groups was mutational in origin. However, the presence of recombination was also detected. The accumulation of mutations in asexual clones leads to the establishment of a network of clone mates. However, this study suggests that the clones primarily originated from the hybridisation between sexual and apomicts.
Keywords: Reproduction; polyploidie; Genetic Variation; rozmnožování; Genetic Loci; Polyploidy; Genotype; Taraxacum; genotyp; genetická variace; genetické lokusy; mikrosatelitní repetice; Microsatellite Repeats